Itsbat Marriage For Parents Who Die And The Legal Consequences: (Case Study: Ruling Of The Kajen Religious Court Number: 1059/Pdt.G/2022/ Pa Kjn) - Noor, Ganis Vitayanty (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
A marriage is valid if it is carried out according to religion/belief and is registered, for those who are Muslim it is recorded at the Religious Affairs Office (KUA) while for non-Muslims it is recorded at the Civil Registration Office (Capil). Marriage registration as proof that the marriage has been carried out. If a person cannot prove their marriage, then the husband and wife concerned must submit a request for itsbat marriage to the Religious Court. Legal marriage also has legal consequences for the rights of the wife and children. So what about those whose parents' marriage dies? And what are the legal consequences of the application for itsbat marriage? In this research, the author uses empirical juridical research methods, with the object of research being the decision of the Kajen religious court number: 1059 Pdt.G/2022/PA Kjn and interviews with related parties. For marriages where the parents have passed away, you can still apply for a marriage itsbat to the Religious Court. Applying for a marriage certificate for parents who have died is a contentious matter. Not all applications for marriage itsbat applications will be granted, but it could be in the form of a lawsuit decision to be withdrawn, a decision to be dismissed, a verstek decision, a decision not to be accepted, and a decision to be rejected. The legal consequence of the decision being granted is that the Petitioner/Petitioners can apply for registration of the marriage of their deceased parents to the Religious Affairs Office (KUA) which is the jurisdiction of the Religious Court which examines, hears and decides the case; The applicant/petitioners can make a birth certificate stating the name of their biological father; The Applicant/Applicants have a civil relationship with their biological father and their biological father's family; The Petitioner/Petitioners have the right to their biological father's assets if their biological father dies. Meanwhile, for court decisions other than those that are granted, you do not have rights similar to the rights obtained for decisions that are granted.